Optimal Fuzzy Regulator - Ahmed, MS (2020)
The conventional design of fuzzy logic controller uses human intuition and experience, which rarely constitutes an optimal design. In this paper, a systematic design procedure is presented to realize the optimal fuzzy logic regulator. The proposed scheme minimizes a suitable criterion function employing the steepest descent method. The recently proposed Block Partial Derivative (BPD) is used to facilitate the gradient computation.